Development of Aerobic Reactors for the Remediation of Textile Effluents by Marine Streptomyces (Asian Journal of Applied Sciences, 2017)
In this study, Streptomyces sviceus KN3 isolated from marine sediments was used to asses its potential for decolorization and detoxification of congo red ,Navy blue and textile azo dye effluent. The decolorization of was initiated on the day 1 and the rate of decolorization increased with increase in time.  The maximum percentage of decolorization 90% and 60% was noticed with Congo red-21, Navyblue-28 dye respectively after 96hrs  of incubation with Streptomyces sviceus KN3.The Aerobic submerged fixed bed reactors were packed with gravel and P-rings as substrates and the gravel based bioreactors exhibited higher efficiency with 99% decolourisation of effluent .The results indicates the suitability of the Aerobic submerged fixed bed reactor  for fermentation of  marine Streptomyces sviceus KN3 and ascertained its potential to provide a practical and cost-effective bioremediation process for the treatment of azo dye effluents.